Transient increase in plasma HIV RNA after COVID-19 vaccination with mRNA-1272 - Bozzi, Giorgio; Lombardi, Andrea; Ludovisi, Serena; Muscatello, Antonio; Manganaro, Lara; Cattaneo, Dario; Gori, Andrea; Bandera, Alessandra (International journal of infectious diseases, 2021)
•COVID-19 vaccination is a promising tool to control the SARS-CoV-2 pandemic.•Vaccinations in people living with HIV have been associated with a transient HIV RNA increase.•We report a case of transient non-suppressible viremia after COVID-19 vaccination.